Effect of Hydrogel Application on Soil Health and Crop Productivity under Soybean-Wheat Cropping System in Indo-Gangetic Plains of India - Sunanda Biswas; Priya Singh; G.A. Rajanna; Anupama Singh (Journal of the Indian Society of Soil Science, 2023)
Soybean-wheat is one of the predominant cropping systems in India. Water productivity in these crops continues to be a challenge and hydrogels have been found effective in conserving soil moisture in critical crop growth stages under rainfed areas. The hypothesis of the present investigation was that the application of hydrogel maintains soil health and crop productivity under water scarcity areas. Therefore, the objective of the present investigation was to study the effect of two types (Pusa hydrogel and K gel) and two rates (2.5 and 5 kg ha-1) of hydrogel application on soil health under various moisture regimes in an Inceptisol. Soil samples were collected from twelve treatments of soybean-wheat cropping system at ICAR-IARI farm, New Delhi after harvesting of crops. Principal component analysis (PCA) was done to identify key soil health indicators. Results showed that the value of soil health index (SHI) ranged from 0.77 to 0.93 and 0.74 to 0.91 after harvesting of soybean and wheat, respectively. Among different types and rates of hydrogel applied in soil, Pusa hydrogel at 2.5 kg ha-1 performed better in maintaining soil health and crop productivity.